2009
DOI: 10.1021/ef800915y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organized Assemblies. Part 5: Study on the Rheology and Stabilization of a Concentrated Coal−Water Slurry Using Saponin of the Acacia concinna Plant

Abstract: The present work involves the preparation of a highly concentrated coal-water slurry employing three different low-rank coals of Indian origin having variable ash content. The formulation, rheology, and stabilization of the slurry have been investigated using saponin extracted from the seeds and pericarps (mods) of the Acacia concinna plant as a dispersant. The saponins extracted from both the seeds and pericarps of the plant are found to stabilize the slurry. The rheological characteristics of the slurry have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 52 publications
2
45
1
Order By: Relevance
“…The similarities in behaviour between Brij-35, a non-ionic surfactant with an anionic surfactant, NaDDBS during the studies on the adsorption studies of these two surfactants at coal-water interface have been reported by Mishra et al [29]. In the stabilization of coal-water slurry by saponin, a natural non-ionic surfactant similarity in the efficiency as additive to that that of anionic surfactants SDS and SDDBS have also been observed [66]. The zeta potential of the mixed system is found to be lower than the pure systems (Fig.…”
Section: Zeta Potential Measurementmentioning
confidence: 58%
See 1 more Smart Citation
“…The similarities in behaviour between Brij-35, a non-ionic surfactant with an anionic surfactant, NaDDBS during the studies on the adsorption studies of these two surfactants at coal-water interface have been reported by Mishra et al [29]. In the stabilization of coal-water slurry by saponin, a natural non-ionic surfactant similarity in the efficiency as additive to that that of anionic surfactants SDS and SDDBS have also been observed [66]. The zeta potential of the mixed system is found to be lower than the pure systems (Fig.…”
Section: Zeta Potential Measurementmentioning
confidence: 58%
“…TritonX-100 even though a non-ionic one, shows a negative potential possibly due to the large number of oxygen atoms of the oxyethylene groups. Literature survey also reveals the similarities of the microenvironment of anionic surfactants and polyoxyethylated non-ionic surfactants [29,[64][65][66]. While probing the micelles of a series of polyoxyethylated non-ionic surfactants [64] and anionic surfactant SDS through the measurements of pK of a number of aldimines we have observed the similarities in the environment provided by these two categories of surfactants.…”
Section: Zeta Potential Measurementmentioning
confidence: 67%
“…The concentration dependent variation in the of binary cationic surfactant mixture may be explained on the basis of availability of counter ion content in the periphery around the micelle [46]. The peripheral region in our case was richer in Br − ion (Table 1) therefore the in this case was close to CTAB.…”
Section: Self-associative Behavior and Interaction Of Surfactant In Mmentioning
confidence: 62%
“…Literature survey also reveals the similarities of the microenvironment of anionic surfactants and polyoxyethylated nonionic surfactants [45][46][47]. In addition, polarization of the water molecules due to the interactions with the oxygen atoms of the oxyethylene groups on the surface of the nonionic micelles is also responsible for negative value.…”
Section: Self-associative Behavior and Interaction Of Surfactant In Mmentioning
confidence: 97%
“…The adsorbance amount increases with an increase of dispersant concentration before adsorbance saturation [5], which results in the sharp decrease of negative zeta potential on coal surface. However, after the saturation point, excessive dispersant molecules arrange on the surface of compact adsorption layer in the opposite direction, resulting in the counteraction of surface electronegativity.…”
Section: Resultsmentioning
confidence: 99%